Depression among carers of AIDS-orphaned and other-orphaned children in Umlazi Township, South Africa. - Kuo, C; Operario, D; Cluver, L (Taylor and Francis, 2012)
South Africa faces the challenge of supporting the well-being of adults caring for growing numbers of AIDS-orphaned children. These adults play a critical role in responses to the epidemic, but little information exists in regard to their mental health needs. This paper reports on findings from n=1599 adults, recruited through representative household sampling, who serve as primary carers for children in Umlazi Township, an HIV-endemic community. Overall, 22% of participants were carers of AIDS-orphaned children, 11% were carers of other-orphaned children and 67% were carers of non-orphaned children. Prevalence of depression was 30.3%. Orphan carers, regardless of whether they cared for AIDS-orphaned or other-orphaned children, were significantly more likely than carers of non-orphaned children to meet the clinical threshold for depression (35.2% vs. 27.9%, p < 0.01). In multivariate logistic regressions, food insecurity and being a female carer were identified as additional risk factors for greater depression. In contrast, households with access to running water and households dependent on salaries as the main source of income were identified as protective factors for disparities in depression. Mental health interventions are urgently needed to address an increased risk for depression among all orphan carers, not just those caring for AIDS-orphaned children.